A Comparison of the Efficacy and Safety of Glimepiride and Sitagliptin in Individuals with type 2 Diabetes Mellitus - Rahul Khobragade (Journal of Biomedical and Pharmaceutical Research, 2018)
Background: One of the main causes of the high cost of treating subjects with Diabetes Mellitus (DM) and society as a whole. Objective: to compare the safety and efficacy of sitagliptin versus glimepiride in subjects with Type 2 DM who are also receiving Metformin treatment as a background. Materials and Methods: From March to September 2018, this research will be carried out in an Indian hospital that offers tertiary care. As an add-on therapy for 12 weeks, eligible subjects were randomized to receive sitagliptin 100 mg and glimepiride 2 mg once per day. Demographic information was entered onto a pre-filled proforma. All research participants/subjects received recommendations to maintain a healthy diet and engage in regular exercise. All subjects had their HbA1C, FBS, weight, Alanine aminotransferase (ALT), serum urea, and serum creatinine measurements taken at week 0 and again at the conclusion of the research at week 12. Attainment of the target HbA1C upper normal limit at research’s conclusion was the main endpoint. Results: The trial enrolled a total of 120 subjects, 60 in each category. In category A, there were 32 men and 28 females, and in category B, there were 36 males and 24 females. When compared to the Glimepiride category, category A using sitagliptin showed a significant decrease in HbA1C and BMI. (p<0.05). FBS reduction was similar between the two categorys (p>0.05). The most common side effects in both categorys were hypoglycaemia, diarrhea, and vomiting. In neither category was there a statistically significant difference in the frequency of occurrence (p>0.05). Conclusion: The results of the current trial provide evidence that sitagliptin is equally effective as glimepiride in improving glycemic control as an add-on medication to metformin and is well tolerated with no significant adverse effects. Sitagliptin outperformed glimepiride and had a lower risk of hypoglycaemia. Additionally, compared to Glimepiride, it was well tolerated and led to weight loss. Key words: Diabetes Mellitus, Sitagliptin, Glimepiride, HbA1C, BMI